Systematic literature review of integrated community case management and the private sector in Africa: Relevant experiences and potential next steps - Phyllis Awor; Jane Miller; Stefan Peterson (Edinburgh University Global Health Society, 2014)
Despite substantial investments made over the past 40 years in low income countries, governments cannot be viewed as the principal health care provider in many countries. Evidence on the role of the private sector in the delivery of health services is becoming increasingly available. In this study, we set out to determine the extent to which the private sector has been utilized in providing integrated care for sick children under 5 years of age with community-acquired malaria, pneumonia or diarrhoea.